Determining tartrate-resistant acid phosphatase in decalcified bone samples pig Sus domesticus - Valencia, Carlos; Franco, Manuel; Pustovrh, Carolina; Salazar, Liliana (Revista Estomatología, 2014)
Introduction: Nowadays, Immunohistochemistry are one of the most important techniques in the histopathological diagnosis. Despite of handling and processing cautions, both of them may generate changes in the protein structure, masking antigens, preventing antibody identification. Among different antigen retrieval methods proposed by the literature, the humid heat with Steamer has been widely accepted for its simplicity, control and low cost.Objective: In this paper a protocol for humid heat antigen retrieval use in bone tissue samples that had been previously fixed in formaldehyde, decalcified with ethylenediaminetetraacetic (EDTA ), and embedded in paraffin is proposed.Materials and methods: Samples of pig’s bone that had been prepared with conventional techniques, from the collection of the pathology laboratory of the University of Valle were used. New fixed process was performed in glutaraldehyde and a steamer was used to enhance antigen exposure. The anti-TRAP DEKOs ®, mouse monoclonal antibody was used as primary antibody, and the KIT UltraVision LP Large Volume Detection System HRP Polymer ® was used as a secondary antibody.Results: In all samples exposed to primary antibody in 1:20 and 1:40 dilutions immunostaining mononuclear cells compatible with preosteoclasts were observed; immunostaining multinucleated giant cells consistent with osteoclasts were described.Conclusions: Humid heat for antigenic recovery is a reliable method for the recovery of bone antigen samples fixed with formaldehyde.